Green and software-defined wireless networks from theory to practice - I, Chih-Lin (Cambridge University Press, 2019)
"Understand the fundamental theory and practical design aspects of green and soft wireless communications networks with this expert text. It provides comprehensive and unified coverage of 5G physical layer design, as well as design of the higher and radio access layers and the core network, drawing on viewpoints from both academia and industry. Get to grips with the theory through authoritative discussion of information-theoretical results, and learn about fundamental green design trade-offs, software-defined network architectures, and energy-efficient radio resource management strategies. Applications of wireless big data and artificial intelligence to wireless network design are included, providing an excellent design reference, and real-world examples of employment in software-defined 5G networks and energy-saving solutions from wireless communications companies and cellular operators help to connect theory with practice. This is an essential text for graduate students, professionals and researchers"--
Keywords: Energieeffizienz; Funknetz; Software-defined networking (Computer network technology); Wireless communication systems / Energy conservation; Wireless communication systems / Energy consumption; Radio resource management (Wireless communications)